Epidemiological profile of deaths from meningitis among elderly pacientes in the state of Paraná from 2013 -2023 (Research, Society and Development, 2025)
Meningitis is an infection of the meninges, the membranes that surround the brain and spinal cord, and can be caused by infectious agents or non-infectious conditions. It is considered a disease with high mortality and is classified as endemic in Brazil. In light of this, the objective of this study was to determine the epidemiological profile of elderly patients who developed meningitis and progressed to death in the state of Paraná, through a descriptive analysis of morbidity and mortality indicators and the most affected regions, based on data provided by the Department of Informatics of the Brazilian Unified Health System (DATASUS). A total of 162,653 cases of meningitis were reported in Brazil between 2013 and 2023, with 8.6% of these cases occurring in elderly individuals, and 9.68% of those within the state of Paraná. A greater fluctuation in case numbers was observed in Paraná in 2021. Among the reported cases, 60.59% were discharged, while meningitis-related deaths accounted for 16.91%, of which 15.1% were male and 19.2% were female. The highest prevalence occurred in the 3rd Regional Health Division. The most affected age group was 70 to 79 years, and most deaths occurred among individuals identified as White. The main etiological cause was bacterial meningitis, accounting for 38.26% of deaths, followed by viral causes at 19.57%. The findings of this study highlight gaps in current disease case management and provide valuable data for future analyses and monitoring of public health conditions.